Laws and policy on biodiversity in Malaysia - Shaik Mohd. Hussain, Shaik Md. Noor Alam; Wan Talaat, Wan Izatul Asma (Sarawak Biodiversity Centre, 2008)
This paper deals with international regimes on biodiversity impacting Malaysia‘s position as a biodiversity rich country. The Convention on Biodiversity (CBD) recognizes the sovereign rights of states to the exclusive use and control over their biodiversity resources. The CBD too expects access to these resources should be made available to others on mutually agreed terms (MAT) subject to prior informed consent (PIC) and on the basis of benefits sharing (BS). Thus ABS (access and benefit sharing) becomes a cornerstone of an international understanding on equitable sharing of the world resources between the technology rich nations and resource rich nations. Concerns have been raised by some that the ABS mechanism may be subverted by TRIPs patentability requirements. The DOHA Declaration and call by some states for inclusion of CBD into TRIPs including disclosure requirement in patent application under TRIPs are central to the current debates over the CBD-TRIPs interface. The Biosafety aspect of biotechnology essentially covered under the Cartagena Protocol obligates member countries in respect of biosafety. The Malaysia Biosafety Act exemplifies this obligation. All these issues are examined in the context of Malaysia‘s NBSAPS (National Biodiversity Strategies and Action Plan 1998).